1999
DOI: 10.1152/ajpregu.1999.276.4.r1164
|View full text |Cite
|
Sign up to set email alerts
|

Glucose regulation of the IGF response system in chondrocytes: induction of an IGF-I-resistant state

Abstract: Nonresponsiveness to the growth-stimulatory actions of insulin-like growth factor (IGF)-I in chondrocytes has been reported in a number of disease states associated with impaired glucose metabolism. Primary rabbit chondrocytes were investigated for changes in their IGF response system [type-I IGF receptor and IGF-binding protein (IGFBP) expression] and in their ability to mount a synthetic response to IGF-I [as35S-labeled proteoglycan ([35S]PG) production] in media containing varying ambient glucose concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Our studies suggested that IGF-1 may rescue the diabetes-induced reduction in SERCA protein abundance and impaired -adrenergic responsiveness (Norby et al 2002(Norby et al , 2004. In addition, diabetic tissues including hearts usually display IGF-1 resistance (Rodgers et al 1995, Kelley et al 1999, Ren et al 1999a, Ren 2000, making glucose clearing by IGF-1 largely dependent on crossreaction with the insulin receptor, which requires higher levels of IGF-1 agonist.…”
Section: Discussionmentioning
confidence: 77%
“…Our studies suggested that IGF-1 may rescue the diabetes-induced reduction in SERCA protein abundance and impaired -adrenergic responsiveness (Norby et al 2002(Norby et al , 2004. In addition, diabetic tissues including hearts usually display IGF-1 resistance (Rodgers et al 1995, Kelley et al 1999, Ren et al 1999a, Ren 2000, making glucose clearing by IGF-1 largely dependent on crossreaction with the insulin receptor, which requires higher levels of IGF-1 agonist.…”
Section: Discussionmentioning
confidence: 77%
“…Glucose serves as a main energy source in chondrocytes (4,5), as a main precursor for glycosaminoglycan synthesis (6, 7), and as a regulator of the cell responses to certain growth factors (44). GLUTs also participate in facilitated transport of glucosamine and N-acetylglucosamine (45,46), which can modify inflammatory responses of chondrocytes (47) and serve as efficient precursors of glycosaminoglycan synthesis (48).…”
Section: Discussionmentioning
confidence: 99%
“…In those circumstances, high extracellular glucose concentrations may counteract TGF effects and eventually those of other anabolic growth factors, such as IGF [Kelley et al, 1999], suggesting that hyperglycemia may be an initiating and/or aggravating factor linking DM to OA.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the extracellular glucose concentration, either increased or decreased, has been shown to directly affect some chondrocyte functions [Kelley et al, 1999;Richardson et al, 2003;McNulty et al, 2005]. In particular, culture of rabbit chondrocytes in either low (<5 mM) or high (25 mM) glucose concentrations decreased proteoglycan synthesis induced by the anabolic growth factor, IGF-I [Kelley et al, 1999]. Exposure to increasing glucose concentrations, dose-dependently decreased dehydroascorbate uptake by human chondrocytes [McNulty et al, 2005], which may have functional implications as dehydroascorbate is essential for collagen synthesis.…”
mentioning
confidence: 99%